2014
DOI: 10.3168/jds.2013-7081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of camel chymosin on the texture, functionality, and sensory properties of low-moisture, part-skim Mozzarella cheese

Abstract: The objective of this study was to compare the effect of coagulant (bovine calf chymosin, BCC, or camel chymosin, CC), on the functional and sensory properties and performance shelf-life of low-moisture, part-skim (LMPS) Mozzarella. Both chymosins were used at 2 levels [0.05 and 0.037 international milk clotting units (IMCU)/mL], and clotting temperature was varied to achieve similar gelation times for each treatment (as this also affects cheese properties). Functionality was assessed at various cheese ages us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 21 publications
8
58
0
4
Order By: Relevance
“…Previous studies have similarly reported lower proteolysis when Cheddar cheese was made with FCC instead of FPC (Bansal et al 2009;Govindasamy-Lucey et al 2010) but these results were attributed to a lower strength of FCC rennet; the rennet strengths used in the first study were ∼0.039 IMCU.g −1 of milk) of FCC and ∼0.058 IMCU.g −1 of milk of calf chymosin and in the second study 0.039 IMCU.g −1 of milk of FCC and 0.0485 IMCU.g −1 of milk of calf chymosin respectively. Moynihan et al (2014), however, also observed lower levels of proteolysis when cheeses were made with FCC added at the same rennet concentration as FPC, consistent with this study. The findings of this study confirm that the proteolytic activity in cheese is reduced even when FCC is used at a similar rennet strength, consistent with reports of the lower proteolytic activity of the isolated enzyme.…”
Section: Proteolysis During Ripeningsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies have similarly reported lower proteolysis when Cheddar cheese was made with FCC instead of FPC (Bansal et al 2009;Govindasamy-Lucey et al 2010) but these results were attributed to a lower strength of FCC rennet; the rennet strengths used in the first study were ∼0.039 IMCU.g −1 of milk) of FCC and ∼0.058 IMCU.g −1 of milk of calf chymosin and in the second study 0.039 IMCU.g −1 of milk of FCC and 0.0485 IMCU.g −1 of milk of calf chymosin respectively. Moynihan et al (2014), however, also observed lower levels of proteolysis when cheeses were made with FCC added at the same rennet concentration as FPC, consistent with this study. The findings of this study confirm that the proteolytic activity in cheese is reduced even when FCC is used at a similar rennet strength, consistent with reports of the lower proteolytic activity of the isolated enzyme.…”
Section: Proteolysis During Ripeningsupporting
confidence: 91%
“…For example, Sheehan et al (2004) showed that reduced-fat Mozzarella cheese made with R. pusillus proteinase resulted in higher levels of pH 4.6 soluble nitrogen during ripening, when compared to cheeses made with either FPC or R. miehei proteinase. The impact of FCC on the properties of Cheddar and Mozzarella has been reported previously (Govindasamy-Lucey et al 2010;Bansal et al 2009;Moynihan et al 2014;Børsting et al 2012). FCC has a much higher ratio of milk clotting activity/general proteolytic activity, known as a C/P ratio, compared to bovine chymosin.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Crescenza C obtained with FPCC and direct-to-vat starter culture showed the significantly highest values of Ha and CW and the lowest values of Ads. FPCC can produce a firmer cheese structure as already reported [23][24][25] also for Crescenza cheese and is probably related to its lower general proteolytic activity than calf chymosin [26] and to the presence of pepsin in calf rennet. On the other hand, Crescenza cheeses that were both obtained with calf rennet but with a different acidifying starter (directto-vat versus bulk starter composed of different biotypes of S. thermophilus) showed smaller differences that could be Crescenza N was manufactured using a direct-to-vat starter culture of St. thermophilus and calf rennet.…”
Section: Effect Of Formulation On Textural Propertiessupporting
confidence: 59%